2018
DOI: 10.21517/0202-3822-2018-41-4-73-85
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Protection Methods for Cryogenic Target Delivery to the Focus of High Repetition Rate Laser Facilities

Abstract: Многоуровневая система защиты криогенной мишени при её доставке в фокус мощной лазерной установки...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(58 reference statements)
0
2
0
1
Order By: Relevance
“…Our study has shown that the shape of the target nest allows one to significantly increase the upper limit of the allowable mechanical overloads on the target and to minimize the injector dimensions. In optimal case the sabot nest should have a conical shape with the angle of 87 0 [4]. A chart of the HTSC-Sabot with the target placed in the conical nest and the cover is shown in Figure 5a.…”
Section: Fst-projectile Assembly Modulementioning
confidence: 99%
See 1 more Smart Citation
“…Our study has shown that the shape of the target nest allows one to significantly increase the upper limit of the allowable mechanical overloads on the target and to minimize the injector dimensions. In optimal case the sabot nest should have a conical shape with the angle of 87 0 [4]. A chart of the HTSC-Sabot with the target placed in the conical nest and the cover is shown in Figure 5a.…”
Section: Fst-projectile Assembly Modulementioning
confidence: 99%
“…To meet the above requirements, the LPI has proposed to use line-moving and free-standing targets to develop a scientific and technological base for repeatable target supply at the laser focus [2][3][4][5]. Precisely moving targets co-operate all production steps in the FST-TL that is considered as a potential solution of mass-production layering and noncontact target delivery in pulsed, repetitively cycled IFE systems.…”
Section: Introductionmentioning
confidence: 99%
“…В соответствии с результатами работы [2] необходимым условием для оптимальной реализации схемы ИТС является формирование криогенных мишеней с изотропным слоем топлива для создания плазмы с интенсивной термоядерной реакцией. Для снижения риска порчи мишени под воздействием тепловых и механических нагрузок, возникающих в процессе доставки в зону ее взаимодействия с лазерным излучением, твёрдый слой топлива должен обладать комплексом новых свойств (по сравнению с равновесным кристаллическим состоянием твёрдых водородов), таких как изотропность, термостойкость и высокая прочность [5].…”
unclassified